Re-casting nature as feminist space in Mad Max: Fury Road. (October 2017) - Yates, Michelle
Abstract : This article shows how Mad Max: Fury Road (2015) transforms nature into a space of feminist possibility. In particular, I show how the film disrupts a dominant narrative within Western environmentalism, what Carolyn Merchant calls the Edenic recovery narrative. The traditional Edenic recovery narrative reproduces the dyadic relationship between woman/nature as passive (object) and man as active agent (subject). Yet, in disrupting the traditional Edenic recovery narrative, Fury Road allows for a representation of female nature that breaks from its traditionally accorded passive status. In the film, female nature gains agency not traditionally accorded to it. In this way, the film draws connections between women and nature, not in the service of capitalist patriarchy, but rather, as Alaimo writes, to re-cast nature as feminist space.